A Comparative Analysis of Sulphur in Azadirachta and its Significance as a Homoeopathic Remedy (Homoeopathy for All, 2025)
India due to its biodiversity is rich in  many forest and mineral resources  which plays a significant role in  enriching the Homoeopathic Materia  Medica and its contribution to a  development of an effective healing  system but are often overlooked  and are seldom used in our daily  homoeopathic prescriptions. This  piece of work focuses mainly on  two closely related remedies one  from plant kingdom (Azadirachta  indica) and another from mineral  kingdom (Sulphur) along with their  identification, basic information  about the drugs.
Keywords: Azadirachta; enriching